2017
DOI: 10.1002/jbm.b.33993
|View full text |Cite
|
Sign up to set email alerts
|

Single‐dose local administration of teriparatide with a octacalcium phosphate collagen composite enhances bone regeneration in a rodent critical‐sized calvarial defect

Abstract: Octacalcium phosphate and collagen composite (OCP/Col) achieves stable bone regeneration without cell transplantation in preclinical studies. Recently, a sponsor‐initiated clinical trial was conducted to commercialize the material. The present study investigated bone regeneration by OCP/Col with the single local administration of teriparatide (parathyroid hormone 1‐34; TPTD). OCP/Col was prepared by mixing sieved granules of OCP and atelocollagen for medical use and a disk was molded. After the creation of a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 31 publications
(76 reference statements)
1
25
0
Order By: Relevance
“…In addition, this study demonstrated that bone regeneration was enhanced more with OCPcolTPTDf than with OCPcol. There could be a similar synergistic effect of OCPcol impregnated with TPTD, as reported recently (Kajii et al, ). However, bone regeneration with β‐TCPcolTPTDf showed no significant differences compared with β‐TCPcol, suggesting that there may be no synergistic effect of β‐TCPcol and TPTD.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In addition, this study demonstrated that bone regeneration was enhanced more with OCPcolTPTDf than with OCPcol. There could be a similar synergistic effect of OCPcol impregnated with TPTD, as reported recently (Kajii et al, ). However, bone regeneration with β‐TCPcolTPTDf showed no significant differences compared with β‐TCPcol, suggesting that there may be no synergistic effect of β‐TCPcol and TPTD.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, it was confirmed that an OCPcol and TPTD composite (OCPcolTPTDf) could enhance bone regeneration as well as OCPcol with the single local administration of TPTD (OCPcolTPTDd) (Kajii et al, ), and these two materials significantly enhanced bone regeneration more than OCPcol alone. Compared with OCPcolTPTDd, OCPcolTPTDf has several advantages.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations